The impact of stimuli color in lexical decision and semantic word categorization tasks - Garrido, M. V.; Prada, M.; Simão, C.; Semin, G. R. (Cognitive Science, 2019)
In two experiments, we examined the impact of color on cognitive performance by asking participants to categorize stimuli presented in three different colors: red, green, and gray (baseline). Participants were either asked to categorize the meaning of words as related to the concepts of “go” or “stop” (Experiment 1) or to indicate if a neutral verbal stimulus was a word or not (lexical decision task, Experiment 2). Overall, we observed performance facilitation in response to go stimuli presented in green (vs. red or gray) and performance inhibition in response to go stimuli presented in red. The opposite pattern was observed for stop-related stimuli. Importantly, results also indicated that color might also be used to categorize neutral stimuli. Overall, these findings provide support to the green-go and red-stop color associations and test the potential functional autonomy acquired by these colors and the boundary conditions to their effects on stimuli categorization.